HUBUNGAN ASUPAN ENERGI, PROPORSI MAKAN MALAM, DURASI TIDUR, DAN AKTIVITAS FISIK DENGAN KEJADIAN GIZI LEBIH PADA GURU DI PERGURUAN MUHAMMADIYAH RAWAMANGUN - Qorirah, Salsabila; Rahayu, Leni Sri (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
The problem that will be studied in this study is about the relationship between energy intake, dinner proportion, sleep duration, and physical activity with the incidence of excess nutrition in Muhammadiyah Rawamangun College. This research uses a type of quantitative research with a cross-sectional design. The population in this study were teachers at SD 24, SMP 31, and SMA 11 Muhammadiyah Rawamangun. Using a total sampling technique with a total sample of 61. Data collection was collected directly, namely in the form of anthropometric measurements, 2x24-hour food recall interviews, filling out sleep duration and physical activity questionnaires. Univariate data will be presented in tabular form. Bivariate data analysis technique with chi-square. Based on the results of the research, it was found that there was a relationship between energy intake (P=0.000), sleep duration (P=0.002), and physical activity (P= 0.000) with the incidence of overnutrition and conversely, there was no relationship between the proportion of dinner energy (P=0.378) with the incidence of overweight. In conclusion, energy intake, sleep duration, and physical activity are related to the incidence of overnutrition, but there is no relationship between the proportion of dinner and the incidence of being overweight among teachers at the Rawamangun Muhammadiyah College.